The Ugly Face of the Labour Market: The Social Organization of Field Education Coordination - Srikanthan, Sinthu (Intersectionalities)

(untitled) (Memorial University of Newfoundland, 2024)
This study uses Dorothy E. Smith’s Institutional Ethnography to examine social work field education coordination in an urban locale in Southern Ontario, Canada. Beginning with the standpoint of racialized students who were searching for a placement—the mandatory, practice-based component of accredited social work programs—I examine how the ruling relations socially organize field education coordination. I draw from textual analyses as well as conversations with key informants: five racialized social work students as well as two field education coordinators. A key finding of the study was that field education represented configurations of race, gender, and class with labour in social work education. By examining how field education coordination amidst the “crisis” of placement shortages was locally and translocally organized, this study explores the ways in which racialized students in one Canadian locale were systematically disadvantaged by neoliberal and managerialist discourses.